Failure and impact resistance analysis of plain and fiber-reinforced-polymer confined concrete cylinders under axial impact loads - Pham, Thong; Chen, Wensu; Hao, Hong (Multi-Science Publishing Co. Ltd., 2018)
This study conducts an experimental and numerical investigation on the failure and impact resistance of plain and fiber-reinforced polymer-confined concrete. The impact resistance of concrete cylinders wrapped with different types of fibers including carbon fiber and glass fiber is examined. Drop-weight tests are utilized to conduct the impact tests while the numerical simulation is conducted using LS-DYNA. The experimental and numerical results have proved that fiber-reinforced polymer can be efficiently used to improve the impact resistance of concrete cylinders. In general, fiber-reinforced polymer ruptures at a lower strain than those in static tests and the rupture strain of glass fiber is much higher than that of carbon fiber. The findings in the experimental tests are confirmed by the numerical results. Glass fiber, therefore, exhibits a much better performance than carbon fiber. It is recommended to use glass fiber to enhance the impact resistance of concrete structures strengthened with fiber-reinforced polymer. In addition, the stress evolution of the specimens is analyzed to investigate the failure mechanism.